Studi Identifikasi Sebaran Ion Logam Pb, Cu, As dan Cd pada Air dan Sedimen di Perairan Bontang Kalimantan Timur Menggunakan Metode Kriging (Ordinary Kriging) - ani, ani ani; Wahidah, Wahidah; Mandang, Idris (GEOSAINS KUTAI BASIN, 2023)
Bontang is one of the cities in East Kalimantan which is geographically located in coastal areas so that it is very vulnerable to marine pollution both from domestic human and industrial activities. This study aims to determine the level and pattern of distribution of poluton metal ions Pb, Cu, As and Cd in water and sediments in Bontang waters using the Kriging (Ordinary Kriging) method. In this study, 4 observation samples were used which were tested in the laboratory to determine the content of heavy metals. Furthermore, the data from laboratory tests along with 4 secondary data were interpolated using the ordinary kriging method with an exponential model to determine the pattern of contour distribution in Bontang waters. The results showed that the heavy metal with the highest distribution value in water and sediment is cadmium with a susceptibility value ranging from 0.006 mg/l to 9.070 mg/l. In general, the pattern of spread of heavy metals originates from coastal areas in a southeasterly direction. The most influential thing on this pattern of spread is tidal currents and bathymetry.